Bagaimana Inovasi Teknologi Hijau Menanggapi Tantangan dan Menentukan Dampaknya? (Yayasan Kawanad, 2023)
Climate change, pollution, and natural resource degradation are among the most pressing environmental challenges faced by the world today. Green technology innovation offers promising solutions to address these challenges by promoting sustainable and environmentally friendly practices. This research aims to understand how green technology innovation responds to environmental challenges and determines its impact on various aspects. Using a qualitative research method with a descriptive-analytical approach, data were collected through literature reviews, in-depth interviews, and document analysis. The findings reveal that green technology innovations, such as renewable energy technologies, clean water and waste treatment systems, and sustainable agricultural practices, effectively reduce greenhouse gas emissions, improve air and water quality, and conserve natural resources. Economically, green technology has created new jobs and driven growth in sectors like manufacturing, energy, and environmental services. Socially, it has enhanced the quality of life by providing better access to clean energy, water, and sanitation, thereby improving public health and reducing poverty. However, the adoption of green technology faces challenges such as high costs, inadequate infrastructure, and low public awareness. Overcoming these challenges requires collaboration between government, private sector, and civil society. With strong commitment and joint efforts, green technology innovation can play a crucial role in achieving sustainable development goals and creating a greener future.